COMBINING ABILITY ANALYSIS IN OKRA [ YSIS IN OKRA [Abelmoschus esculentus Abelmoschus esculentus (L.) Moench] (L.) Moench] - NEETU, RAKESH KUMAR AND ANAND KUMAR SINGH, (The Bioscan, 2018)
A study was conducted to estimate the combining ability analysis through the best combiners for yield and quality parameters in okra. Thirty six F1 generated by line × tester mating design these F1s along with 15 parents and commercial check were evaluated in Randomized Block Design with three replications at Vegetable Research Farm, Banaras Hindu University, Varanasi, during 2012 and 2013. The line IC-212267 for Days at first flowering (-8.44), Days at 50% flowering (-8.55) and Plant height (11.59), Pusa Makhmali for number of branches plant-1 (1.02), Kashi Kranti for internodal length (-0.52) and fruit length (3.76), SA-29 for fruit diameter (0.25), IC140927 for average fruit weight (1.47), number of fruits plant-1 (2.18) and total fruit yield q/hectare (26.43) were identified as good general combiners. In order of merit the crosses IC-43742 × Varsha Uphar (-5.84) IC-43742 × Varsha Uphar (-5.95) IC-85814 × Varsha Uphar (12.88) IC-140927 × Hissar Unnat (1.48) IC-43742 × VRO5 (-0.87) VRO-6 × Varsha Uphar (4.73) Pusa Makhmali × VRO-5 (2.82) VRO-3 × Varsha Uphar (0.25) Pusa Makhmali × VRO-5 (2.37) SA-29 × Varsha Uphar (45.57) were identified as good specific combiners. The present study reveals good scope for commercial exploitation of heterosis in okra.